Swarm Intelligence Based Protein Conformational Search Algorithm. - Bahamish, Hesham Awadh Abdallah; Abdullah, Rosni; Salam, Rosalina Abdul (2007)
There is no doubt of the role that proteins play in the biological processes inside the human body. Proteins can perform their function only when they fold into their tertiary structure. The thermodynamics hypothesis formulated by Anfinsen stated that the tertiary structure of a protein in its physiological environment is the conformation with the lowest free energy.